1999
DOI: 10.1074/jbc.274.49.34691
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase D Stimulation by Receptor Tyrosine Kinases Mediated by Protein Kinase C and a Ras/Ral Signaling Cascade

Abstract: Stimulation of phospholipase D (PLD) in HEK-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…The activation of PLD by EGF is dependent upon RalA (23,45), as was the EGF receptor endocytosis reported here. Consistent with these data, RalA was recently reported to be required for EGF-induced receptor endocytosis (29).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The activation of PLD by EGF is dependent upon RalA (23,45), as was the EGF receptor endocytosis reported here. Consistent with these data, RalA was recently reported to be required for EGF-induced receptor endocytosis (29).…”
Section: Discussionmentioning
confidence: 75%
“…It was recently reported that EGF-induced PLD activity is dependent upon RalA (23,45), a Ras family GTPase (9) that is associated with PLD1 (14,25). The generation of EGFR cells that also overexpress either wild-type RalA or a dominant negative allele of RalA (S28N) was described previously (23).…”
Section: Fig 2 Egf-induced Receptor Degradation Is Inhibited By Primentioning
confidence: 99%
“…Studies with pertussis toxin (PTX) and PKC inhibitors, furthermore, suggested that this potentiation of PLC stimulation by GPCRs is mediated by G i type G proteins and involves activation of a PKC isoenzyme (8,9). Since GPCRs and RTKs activate distinct PLC isoenzymes and by distinct mechanisms, we wondered whether GPCRs may also induce sensitization of PLC stimulation by RTKs endogenously expressed in HEK-293 cells (10,11). We report here that short term activation of GPCRs can induce a long lasting up-regulation of PLC stimulation by EGF and PDGF but not insulin.…”
Section: Stimulation Of Phosphoinositide-hydrolyzing Phospholipase C mentioning
confidence: 79%
“…For instance, TSC and PLD are both modulated by mitogens (e.g., serum and insulin) [40][41][42][43][44][45][46] and TNFα. 15,47 The Ras-Raf-MEK-Erk pathway inhibits TSC2 via phosphorylation by either Erk 48,49 or a downstream kinase Rsk, 50 at the same time PLD activation by Ras [51][52][53][54] or Erk 54,55 has also been suggested. Most recently, our studies have uncovered a direct interaction between Rheb and PLD1.…”
Section: Pld1 As An Effector Of Rheb In Mtorc1 Signalingmentioning
confidence: 99%